Pasca pandemi covid-19 dampaknya terhadap strategi pemasaran online dalam meningkatkan penjualan produk - Saifulloh, Moh (Maliki Interdisciplinary Journal, 2024)
This research also aims to identify factors that influence the success of online marketing strategies in increasing product sales in the post-pandemic era. The research approach used is the case study method. Research data was collected through interviews with marketing managers and strategic decision makers in companies active in online marketing in Indonesia. Apart from that, data analysis was also carried out through literature reviews and secondary data analysis related to the impact of the COVID-19 pandemic on online marketing and product sales in Indonesia. The results of this research will provide a deeper understanding of the impact of the COVID-19 pandemic on online marketing strategies and product sales in Indonesia. This research will identify best practices in post-pandemic online marketing strategies that can increase product sales. Apart from that, it is also hoped that this research can reveal the factors that contribute to the success of online marketing strategies in the post-pandemic era.